The Impact of Multilingualism on Translation Strategies - Ulmasova Mehribon Uktam Qizi; Nilufar Khalimova (Indonesian Journal Publisher, 2026)
In the current era of globalization, cultural and linguistic exchange has grown at an unprecedented rate. These changes have also had an impact on the field of translation. At the heart of these changes are linguistic concepts such as descriptive translation, bilingualism, multilingualism, and code-switching (speaking alternatively between two or more languages). This article explores one of the above concepts – multilingualism – and its importance in translation. It discusses the significances of conveying the text correctly, taking into account both the reader and the content of the text, and preserving the originality of the text through new translation methods or directly conveying its meaning. The same time, the results of the survey on the importance of the multilingualism are also analysed and presented.